A case report of exacerbation of extrapyramidal symptoms following the switch from risperidone to paliperidone during valproate therapy - Emi Hata; Masatoshi Miyauchi; Nobuhiko Noguchi; Takeshi Asami (BMC Psychiatry)
Abstract Background Paliperidone is a second-generation antipsychotic and the main active metabolite of risperidone, formulated to provide consistent therapeutic effects through an extended-release system, designed to provide consistent therapeutic effects through an extended-release formulation. While commonly used in clinical practice, switching from risperidone to paliperidone, particularly during valproate therapy, can pose challenges due to potential pharmacokinetic interactions that may increase the risk of extrapyramidal symptoms (EPS). Despite clinical observations suggesting these interactions, case reports documenting such adverse effects are scarce. Case presentation. We report a case of a 48-year-old Japanese male with epilepsy-associated psychosis and mild intellectual disability who experienced severe EPS during a gradual cross-titration from risperidone to paliperidone while on valproate therapy. The patient had a history of well-controlled epilepsy with valproate and developed auditory hallucinations, delusions, and psychomotor agitation at age 48. Initial treatment with risperidone was partially effective but did not sufficiently manage his psychotic symptoms, prompting a switch to paliperidone. Shortly after increasing the paliperidone dose, the patient developed significant EPS, including muscle rigidity and elevated creatine kinase levels, indicative of potential neuroleptic malignant syndrome. Paliperidone was immediately discontinued, leading to a marked improvement in symptoms. Discussion This case highlights the pharmacokinetic interaction between valproate and paliperidone, which can elevate plasma levels of paliperidone and exacerbate EPS. Literature suggests that valproate can prolong the gastrointestinal retention time of paliperidone, leading to increased absorption and enhanced dopaminergic blockade. The gradual cross-titration method may have compounded these effects, emphasizing the need for careful dose adjustments and monitoring during antipsychotic switching, especially in patients on concomitant valproate therapy. Conclusion The findings suggest that direct substitution methods, rather than gradual cross-titration, may be safer when switching from risperidone to paliperidone, particularly in patients receiving valproate. Clinicians should be aware of the potential interactions and closely monitor for signs of EPS during such therapy adjustments.